Interaction between Students' Learning and Early Mathematical Skills to Increase Mathematical Critical Thinking Skills - Yumiati, Yumiati; Kusumah, Yaya (Universitas Islam Raden Intan Lampung, INDONESIA, 2019)
The aim of this study is to determine the interaction between learning factors (CORE and conventional) and the initial mathematical skills factor (KAM) to increase mathematical critical thinking skills (KBKM) of students. The method used in this study was quasi-experimental with the non-equivalent group pretest-post design. The data analysis used was two-way ANAVA test. The results of the study are (1) There is no interaction between learning factors with KAM factors (2) the improvement students’ mathematical critical thinking skills in the CORE (connecting, organizing, reflecting, extending). learning group is higher than the conventional learning group for each KAM group (3) In both learning groups, the improvement of the students’ mathematical critical thinking skills in the upper KAM level is higher than the middle and lower KAM level and the improvement in the middle KAM level is higher than the lower KAM level.